Unveiling the cold reality of metamorphic proteins - Andy LiWang; John Orban (Proceedings of the National Academy of Sciences, 2025)
Metamorphic proteins switch reversibly between two differently folded states under a variety of environmental conditions. Their identification and prediction are gaining attention, but the fundamental physicochemical basis for fold switching remains poorly understood. In this Perspective article, we address this problem by surveying the landscape of well-characterized metamorphic proteins and noting that a significant fraction of them display temperature sensitivity. We then make the case that the dependence on temperature, in particular cold-denaturation effects, is likely to be an underlying property of many metamorphic proteins regardless of their ultimate triggering mechanisms, especially those with a single domain. The argument is supported by rigorous analysis of hydrophobic effects in each well-characterized metamorphic protein pair and a description of how these parameters relate to temperature. The conclusion discusses the relevance of these insights to a better understanding of prediction, evolution, and de novo design strategies for metamorphic proteins.